2000
DOI: 10.1097/00003246-200005000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil-supplemented parenteral diets normalize splanchnic blood flow and improve killing of translocated bacteria in a low-dose endotoxin rat model

Abstract: In this model, diets enriched with fish oil abolish the endotoxin-induced decrease of nutritive blood flow to the gut and ameliorate the bactericidal defense of the splanchnic region. The lower count of viable bacteria in the fish oil groups is more related to an improved killing of translocated bacteria than a reduction of the translocation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
5

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 29 publications
2
35
0
5
Order By: Relevance
“…Heller AR et al [20] found that after a major abdominal tumor surgery, fish oil supplementation could improve liver and pancreas function. Animal experiments have demonstrated improved perfusion and fewer translocations of viable bacteria from the gut into the mesenteric lymph nodes and liver after omega-3 fatty acid infusion in rats [22,23] . Therefore, our results suggest that parenteral nutrition supplemented with omega-3 fish oil might protect liver function after a major abdominal operation in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Heller AR et al [20] found that after a major abdominal tumor surgery, fish oil supplementation could improve liver and pancreas function. Animal experiments have demonstrated improved perfusion and fewer translocations of viable bacteria from the gut into the mesenteric lymph nodes and liver after omega-3 fatty acid infusion in rats [22,23] . Therefore, our results suggest that parenteral nutrition supplemented with omega-3 fish oil might protect liver function after a major abdominal operation in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mice fed fish oil and then injected with LPS had lower plasma TNF-α, IL-1β and IL-6 concentrations than mice fed safflower oil (Sadeghi et al 1999), while fish oil-containing parenteral nutrition decreased serum TNF-α, IL-6 and IL-8 concentrations in burned rats Tashiro et al 1998). Total parenteral nutrition using fish oil as the lipid source was found to prevent the LPS-induced reduction in blood flow to the gut and to reduce the number of viable bacteria in mesenteric lymph nodes and liver following exposure to live bacteria (Pscheidl et al 2000). Fish oil did not, however, decrease bacterial translocation across the gut, and the authors concluded that fish oil must have improved bacterial killing.…”
Section: Systemic Inflammatory Response To Injurymentioning
confidence: 95%
“…Experimental studies show that FO may influence the response to LPS: FO increases survival in guinea pigs submitted to lethal doses of LPS [14], improves splanchnic and vital organ hemodynamics, and reduces bacterial translocation [15]. This is also observed in critically ill patients with acute inflammatory conditions such as ARDS sepsis and surgery receiving FO with parenteral nutrition [13].…”
Section: Modulation Of the Physiological Response To Lpsmentioning
confidence: 96%